2007
DOI: 10.1097/01.aog.0000267200.70965.a5
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrician–Gynecologists' Knowledge and Practice Regarding Human Immunodeficiency Virus Screening

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Young, pregnant, Hispanic and African-American patients were most likely to report that HIV testing had been recommended by their obstetrician-gynecologist. Similar to the perceptions of obstetrician-gynecologists [21], patients indicated they most commonly decline testing because of seeing themselves as low risk [23]. …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Young, pregnant, Hispanic and African-American patients were most likely to report that HIV testing had been recommended by their obstetrician-gynecologist. Similar to the perceptions of obstetrician-gynecologists [21], patients indicated they most commonly decline testing because of seeing themselves as low risk [23]. …”
Section: Resultsmentioning
confidence: 97%
“…Gray and colleagues [21] found that 97% of ob-gyns adhere to ACOG guidelines [22] and recommend HIV testing to all pregnant patients; ACOG recommends that this be done as early in the pregnancy as possible and with the opt-out method of screening where legally possible [22]. Most (83.3%) of those who see pregnant patients reported feeling at least moderately knowledgeable regarding HIV in pregnancy, and 92% reported maintaining contact with an infectious disease specialist for consultation [21].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations